No Impact of Calorie or Unit Information on Ad Libitum Alcohol Consumption. (18th September 2017) - Maynard, Olivia M; Langfield, Tess; Attwood, Angela S; Allen, Emily; Drew, Imogen; Votier, Alex; Munafò, Marcus R
Abstract: Aims: To investigate the impact of unit and calorie information on drinking behaviour in an ad libitum taste test paradigm. Methods: In this experimental human laboratory study, participants were randomized to one of four conditions, balanced by gender, using a 2 (unit information: present vs. absent) × 2 (calorie information: present vs. absent) between-subjects design. The percentage of beer consumed during the taste test was the primary outcome measure. Results: Among this largely undergraduate student population, we found no evidence that either unit or calorie information impacted alcohol consumption in an ad libitum taste test. A manipulation check indicated that few of the participants receiving either unit and/or calorie information could accurately recall the number of units and/or calories in the beverages provided to them, indicating low levels of engagement with this information. Analysis of qualitative reactions to calorie and unit labelling indicated possible negative unintended consequences of calorie and unit information, including using unit information to facilitate consumption of higher strength beverages, and calorie information to reduce food consumption prior to a drinking episode. Conclusion: We find no evidence to support an effect of unit or calorie information, a public-health initiative supported by the alcohol industry, on drinking behaviour. It is possible that compulsory unit and calorie labelling, at least in the numeric format used here, would have no effect on alcohol intake and may even have some negative unintended consequences among certain populations.